KEKAYAAN JENIS DAN FUNGSI POHON PENGHIJAUAN DI PANTI ASIH PAKEM, SLEMAN - , PURI AYU LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Asih Orphanage including one of private institution which has ample land and plant species richness due to greening. So far, there vwas no available information about species richness in that institution. Therefore, the author intended to determine the species compostion, distribution and function of plants in Asih Orphanage. This study begans with a survey, and data collection was conducted by using 100% plant census. Each plant recorded the type, number, life level, and existence position at Asih Orphanage.. The results showed that the Orphanage had the richness of plants as many as 30 type of plants species in 24 families, 152 individuals. As for the details, namely: 7 types of stake as many as 25 individuals, and 23 species of plants type as many as 127 individuals. These species have four functions including amemnity tree, fruit-bearing, wood-producing and tree-producing. The overall composition types are as follows: Famili Moraceae (Artocarpus heterophllus), Anacardiaceae (Mangifera indica, Spondias pinnata), Agavaceae (Cordyline frusticosa), Podocarpaceae (Podocarpus neriifolius), Myrtaceae (Eugenia aquea, Psidium guajava),Oxalidaceae(Averrhoa carambola), Apocynaceae (Plumeria acuminate), Fabaceae (Leucaena leucosephala, Falcataria molucana, Maniltoa grandiflora), Sapindaceae (Nephelium Lappaceum, Filicium decipiens, Dimocarpus longan),Annonaceae (Polyathia longifolia, Annona muricata), Burseraceae (Canarium commune),Arecaceae (Cocos nucifera), Cupressaceae (Cupresus getusa), Gnetaceae (Gnetum gnemon), Verbenaceae (Tectona grandis), Sterculiaceae(Theobroma cacao),Meliaceae (Swietenia mahagoni), Sapotaceae (Manilkara zapota), Combretaceae (Terminalia catappa),Casuarinaceae (Casuarina montana), Lauraceae (Litsea chinensis), Araliaceae (Schefflera scandens), Muntingiaceae (Muntingia calabura).